Third Five-Year Plan of Kolar District - Planning Commission (Planning Commission, 1965)
Kolar District is in the east of Mysore, situated between 12° 48' and 13° 58' north latitude and 77° 22' and 78° 35' east longitude. Its greatest length is from north to south, about 85 miles, but from east to west an equal distance may be measured between the farthest points.
Government of Mysore, Planning, Housing and Social Welfare Department